How active are right-wing party members? Portuguese right-wing delegates, from a comparative and a General Incentives Model (GIM) perspective - Espirito Santo, Paula Maria Ferreira (2023)
This contribution explores the role of the incentives and benefits of party affiliation, along with the ideological reasons for being politically active, in particular as a party delegate. The rational for party affiliation and for activism has developed over recent decades, ranging from individual to collective reasons. The incentives that explain activism have been an essential part of the discussion on the reasons for becoming a party member, particularly following the seminal study on the General Incentives Model (GIM)’s, Seyd and Whiteley (1992). Later developments from Whiteley et al. (2019) provided evidence on the activism of radical political forces, as is the case of UKIP in the United Kingdom. Following the GIM framework, this study explores these themes within a Portuguese context, and from a comparative perspective. To date, investigations in this field have rarely focused on Portugal. The research question is: how do delegates view their party’s incentives and benefits, and how is this influenced by their ideological self-positioning on the left–right scale? We argue that the larger the party, the lower the members’ assessment will be of the incentives and benefits achieved. In methodological terms, this study is based on the MAPP project and surveys, applied to Portuguese political party members, including delegates from right-wing parties. The relevance of this article lies in the application of the GIM to delegates of right-wing political parties, in a comparative perspective, considering a downward trend and a Southern European country that has, to date, been little explored in this context (Sierens et al. 2022). The goal is to find evidence of how right-wing party members and delegates view the incentives and benefits that play a role in party activism.